2010
DOI: 10.1007/s10869-010-9181-6
|View full text |Cite
|
Sign up to set email alerts
|

What Reviewers Should Expect from Authors Regarding Common Method Bias in Organizational Research

Abstract: ■Many researchers have suggested that meeting time, scope, and budget goals, sometimes called 'project efficiency,' is not the comprehensive measure of project success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
1,400
2
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,916 publications
(1,436 citation statements)
references
References 45 publications
23
1,400
2
11
Order By: Relevance
“…Finally, as the focus of this study was on perceived rather than objective ethical culture and well-being, using self-reports was the most relevant method (see, e.g., Conway & Lance, 2010).…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Finally, as the focus of this study was on perceived rather than objective ethical culture and well-being, using self-reports was the most relevant method (see, e.g., Conway & Lance, 2010).…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…All measures in the study are self-reported. Self-report has been argued to be appropriate for variables that are perceptual or related to private events (Chan, 2009;Conway and Lance, 2010). Self-report ratings are not considered to be inferior to other type of subjective rating, such as supervisor or peer rating (Conway and Lance, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore some individuals may have underreported their exposed to cyberbullying as acknowledgement of victimisation could prompt feelings of vulnerability (van Beest & Williams, 2006). Attempts were made to reduce the risk of common method bias as the anonymous treatment of study results was outlined and participants were clearly advised that they could withdraw from the research at any time (Conway & Lance, 2010).…”
Section: Study Limitationsmentioning
confidence: 99%